Optimizing Facebook-Based Digital Marketing Strategies at Tadika Al Fikh Orchard Parklands, Malaysia - Muhammad Alfharuq Aditya A. Hasibuan; Syahrul Amsari (International Conference on Islamic Economic (ICIE), 2026)
Analyzes the optimization of Facebook-based digital marketing at Tadika Al-Fikh Orchard Parklands, an Islamic early childhood education institution in Malaysia facing a sharp enrollment decline, from 32 students in 2022 to 13 in 2025. The research problem covers three aspects, namely the management of digital marketing from a human resource perspective, the reasons Facebook Ads has not been utilized, and the effectiveness of Facebook in attracting parental interest and trust. This study uses a qualitative method with a descriptive approach. Data were collected from six purposively selected informants, an account manager, two teachers, and three parents, through semi structured interviews, participant observation of the institution's Facebook account, and documentation. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, covering data condensation, data display, and conclusion drawing. The findings show that Facebook management is handled by a single person for all branches, which limits content consistency. Facebook Ads has not been utilized due to budget constraints, limited technical competence, and the fact that the account used is a personal profile rather than an official Facebook Page, which structurally cannot activate paid advertising features. Facebook marketing is found to be effective in building initial awareness among parents but has not yet been effective in converting that awareness into enrollment decisions. The study concludes that migrating to an official Facebook Page, strengthening human resource capacity, and allocating a dedicated advertising budget are essential steps to optimize the institution's digital marketing strategy.